Selection of suitable reference gene for gene expression studies of porcine ovaries under different conditions in quantitative reverse transcription polymerase chain reaction assay - Kim, Hwan-Deuk; Jeon, Hye-Jin; Jang, Min; Bae, Seul-Gi; Yun, Sung-Ho; Han, Jee-Eun; Kim, Seung-Joon; Lee, Won-Jae (Journal of animal reproduction & biotechnology (Online), 2022)
The ovary undergoes substantial physiological changes along with estrus phase to mediate negative/positive feedback to the upstream reproductive tissues and to play a role in producing a fertilizable oocyte in the developing follicles. However, the disorder of estrus cycle in female can lead to diseases, such as cystic ovary which is directly associated with decline of overall reproductive performance. In gene expression studies of ovaries, quantitative reverse transcription polymerase chain reaction (qPCR) assay has been widely applied. During this assay, although normalization of target genes against reference genes (RGs) has been indispensably conducted, the expression of RGs is also variable in each experimental condition which can result in false conclusion. Because the understanding for stable RG in porcine ovaries was still limited, we attempted to assess the stability of RGs from the pool of ten commonly used RGs (18S, B2M, PPIA, RPL4, SDHA, ACTB, GAPDH, HPRT1, YWHAZ, and TBP) in the porcine ovaries under different estrus phase (follicular and luteal phase) and cystic condition, using stable RG-finding programs (geNorm, Normfinder, and BestKeeper). The significant (p< 0.01) differences in Ct values of RGs in the porcine ovaries under different conditions were identified. In assessing the stability of RGs, three programs comprehensively agreed that TBP and YWHAZ were suitable RGs to study porcine ovaries under different conditions but ACTB and GAPDH were inappropriate RGs in this experimental condition. We hope that these results contribute to plan the experiment design in the field of reproductive physiology in pigs as reference data.